Effect of temperature on tribological properties of 1-butanol–diesel fuel blends – Preliminary experimental study using the HFRR method. (15th July 2021) - Kuszewski, Hubert; Jakubowski, Mirosław; Jaworski, Artur; Lubas, Janusz; Balawender, Krzysztof
Highlights: Lubricity tests using the HFRR method for the 1-butanol–diesel fuel blends were presented. Microscopic photographs of the test ball wear scars were presented. The lubricity tests were conducted at various fuel temperatures. The results of the lubricity tests were referenced to the standard requirements. Abstract: It has been shown that 1-butanol cannot be used as a self-contained fuel in typical diesel engines, mainly due to its low propensity for self-ignition and its low lubricity; thus, increasing attention is being paid to 1-butanol–diesel fuel blends (1-BDFs). In turn, considering the durability of fuel injectors, it is important to test the lubrication of fuels at increased temperatures, while varying the conditions under which the lubricating layer is formed. The article evaluates the lubricity of standard diesel fuel and 1-BDFs at temperatures of 30, 60, 90 and 120 °C. Tests were carried out for 1-BDFs at volume fraction of 1-butanol of 5, 15, 25%, using the high-frequency reciprocating rig (HFRR) method. For individual fuel samples, microscopic photos of the wear scar on the test balls are presented, along with the marked areas, which were taken into account when measuring the diameters of the wear scars. The wear scar diameter (WSD) values were adopted as the basic criterion for assessing lubricating properties. The results showed that larger fractions of 1-butanol in a blend contributed to improved lubricity at the highest sample temperature analysed, and the largest differences in lubricating properties at changes in the sample temperature were observed for neat diesel fuel (NDF) and for 1-BDF with a 5% 1-butanol volume fraction. Test results at 60 °C also showed that 1-BDFs with a 1-butanol volume fraction up to 25% meets lubricity requirements specified in EN 590 and ASTM D975.